Development of Eu3+-doped phosphate glass for red luminescent solid-state optical devices - P. Aryal (2020)
© 2020 Eu3+-doped lithium phosphate glasses, (63-x) P2O5–32Li2O–5Al2O3‒xEu2O3, where 0≤x≤5 mol% concentrations were prepared by conventional melt-quenching technique. The glasses were characterized through various physical and optical properties at room and low temperatures (10K). The radiative transition probability, stimulated emission cross-section, branching ratio and radiative lifetime of the glasses were evaluated following the Judd-Ofelt theory. Two-fold increase in the photoluminescence (PL) intensity was observed under 394 nm excitation at 10K as compared to that measured at room temperature. The absence of 7F1→5D3,1 excitation transition at 10K was found due to a decrease in thermal energy of ground states. The presence of O2−−Eu3+ charge transfer excitation band (CTB, 200–275 nm) was observed. An optimum PL emission was recorded in the glass with 3 mol%, whereas the concentration quenching was noticed for the sample with 5 mol%. The results show that the Eu3+-doped lithium phosphate glasses could be potential candidates for red laser applications.